Peran Kaum Perempuan Desa Wudi dalam Upacara Roko Molas Poco - Nggias, Falensia Fitria; Wiasti, Ni Made; Suarsana, I Nyoman (Sunari Penjor : Jurnal of Anthropology, 2023)
Women in the roko molas poco ceremony have an important position, because this ceremony is related to the values ??and symbols of Manggarai women. This ceremony is a rite of carrying (roko) the main pole of traditional house (siri bongkok) which is symbolized as a beautiful girl (molas) who comes from the mountain (poco) and paraded to the site of the traditional house (Mbaru Gendang). The purpose of this study is to find out the role of woman in the roko molas poco ceremony. The method used in this research is a qualitative descriptive method with an ethnographic research model through observation, interviews, and literature studies. The theory used is role theory and ecofeminism theory. Based on research, the ceremony divided it four stages, namely preparation stage, implementation stage, construction stage, and the house blessing stage. The role of women in the ceremony is that women are involved in the molas poco pick-up group, as friends of molas poco and involved in the contruction of the drum house.